Glutaric aciduria type I: ultrasonographic demonstration of early signs - Forstner, Rosemarie; Hoffmann, Georg F.; Gassner, Ingemar; Heideman, Peter; De Klerk, Johannis B. C.; Lawrenz-Wolf, Burghard; Doringer, Ernst; Weiß-Wichert, Peter; Tröger, Jochen; Colombo, Jean P.; Plöchl, Engelbert (Pediatric radiology, 1999)
Glutaric aciduria type I (GA-I) is a rare inherited metabolic disease with increased excretion of glutaric acid and its metabolites. Diagnosis is often delayed until the onset of irreversible neurological deficits.
Gesehen am 22.01.2021